Measurement of Vapour Pressure and Heats of Sublimation of o-Nitro Benzyl Chloride by Knudsen Effusion Method - Mohammad Ali Hosseini, Sayed; Naghibi, H.; H. Peikar, M.; Jamalizadeh, E. (Asian Journal of Chemistry, 2010)
An experimental method based on Knudsen effusion apparatus has been designed to measure very low vapour pressure of benzoic acid and o-nitro benzyl chloride at different temperatures and by means of the well known Clausius-Clapyron relationship and from slope of the logarithm of the vapour pressure against reciprocal of absolute temperature. Heats of sublimation are calculated for benzoic acid ΔHsub = 91.74 ± 3.45 kJ mol–1 and for o-nitro benzyl chloride ΔHsub = 96.20 ± 3.45 kJ mol–1. The precision measurements of vapour pressure and heats of sublimation have been tested using benzoic acid; the results are in good agreement with literature values.